Pengaruh Pengetahuan, Kepercayaan dan Risiko terhadap Minat Pengguna Financial Technology Peer to Peer Lending pada Pemilik UMKM Fashion di Kota Surakarta - Siti Khumairoh; Fadjar Harimurti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze (1) the influence of knowledge on interest in users of peer to peer lending financial technology among fashion MSME owners in the city of Surakarta. (2) the influence of trust on interest in peer to peer lending financial technology users among fashion MSME owners in the city of Surakarta. (3) the influence of risk on interest in users of peer to peer lending financial technology among fashion MSME owners in the city of Surakarta. The objects of this research are 100 MSMEs in the fashion sector in the city of Surakarta. The data analysis techniques used are regression analysis, t test, F test, coefficient of determination test (R2). The research results show that: (1) Knowledge has a significant positive effect on interest in users of peer to peer lending financial technology among fashion MSME owners in the city of Surakarta. (2) Trust has a significant positive effect on interest in users of peer to peer lending financial technology among fashion MSME owners in the city of Surakarta. (3) Risk has a significant negative effect on interest in users of peer to peer lending financial technology among fashion MSME owners in the city of Surakarta.